Dielectric analysis of polypropylene (PP) and polylactic acid (PLA) blends reinforced with halloysite nanotubes. (August 2018) - Rajan, Krishna Prasad; Al-Ghamdi, Ahmed; Thomas, Selvin P; Gopanna, Aravinthan; Chavali, Murthy
Polypropylene (PP) and polylactic acid were blended in the ratio 80:20 by weight and compatibilized with 3 wt% of maleic anhydride-grafted-PP. The compatibilized blend was chosen as the base matrix for reinforcement with halloysite nanotubes (HNTs). The nanotube content varied from 0 to 10 wt%. Blend and the nanocomposites were prepared by melt mixing technique. Dielectric analysis of the base matrix and the nanocomposites was carried out using interdigitated electrode sensor in a DEA 288 Epsilon-dielectric analyser. The dielectric properties of the composites were measured at temperatures from 30 to 120°C at various frequencies ranging from 1 Hz to 1 kHz. Permittivity values slightly decreased as the HNT content increased from 0 to 2 wt%. It increased at 4 wt% of HNT and again slightly decreased at 6 wt% of HNT, and with further increase in HNT (HNT 8 and HNT 10) led to increase in permittivity values. Loss factor values decreased slightly as the HNT content in the composites increased from 0 to 4 wt%; but with further increase in HNT, the loss factor showed a sharp increase. Loss tangent (tan δ ) values decreased up to 4 wt% of HNT (HNT 4) and then increased up to 8 wt% (HNT 8) of HNT and then decreased slightly (for HNT 10). Analysing the different dielectric properties, consistent properties were shown by 6 wt% of HNT similar to static and dynamic mechanical properties. The analysis showed that the composites can be utilized in microelectronic devices or in microelectronic packaging applications.